Elasticidades dinâmicas da balança comercial da agropecuária brasileira: uma análise do período 2000-2019 - Azevedo, Dalylla Soares de (2021)
The main objective of this study is to test the hypothesis that there is a long-term, timevarying relationship between the Brazilian agricultural trade balance and its main determinants (real exchange rate, domestic income and external income). The economic transformations that have taken place in recent decades and the shocks to which emerging economies, such as Brazil are subject to, offer a good opportunity for investigations of this nature. The econometric methodology used follows Bierens and Martins (2010), who modeled time-varying cointegration vectors through the introduction of Chebyshev temporal polynomials. Based on a sample for the period from January 2000 to July 2019, the Bierens and Martins (2010) test rejects the hypothesis according to which long-term Brazilian foreign trade elasticities are time-invariant. The results indicate that the elasticity of net exports of Brazilian agriculture in relation to the real exchange rate was positive and elastic in practically the entire period considered. Positive and elastic effects were also observed regarding external demand. On average, increases of 10% in the real exchange rate and in foreign income increase net Brazilian agricultural exports by 22.2% and 17.6%, respectively. Household income had a negative impact, but with inelastic effects and less variability.